Singaporeans as 'post-tourists' - insights into a contemporary form of tourism. - Sim, Sok Yin. (2013)
In this article, I explore the touristic experiences of young Singaporeans to explicate how they have taken on the role of the ‘post-tourist’, embracing a contemporary form of tourism which indicates a shift away from the package tour. Also, I argue that these individuals are able to negotiate reflexivity and authenticity through their actions. Drawing on in-depth data from interviews with young adults, I suggest that the Mcdonaldization of society plays an important role in causing the shift away from the package tour. Besides, the data shows that in contemporary society, the desire for new touristic experiences and advancement in technology have shaped new touristic encounters for these ‘post-tourists’. Finally, the study concludes that while these ‘post-tourists’ can encounter new experiences, the larger structural constraints are still evident. Taken together, the findings suggest the rise and proliferation of new forms of tourism in Singapore, and how individuals can negotiate their touristic identities and experiences.